A Case Study to Improve Pronouncing English Consonant Clusters by Young Yemeni Learners in Malaysia (International Journal of Language, Literacy and Translation, 2019)
Acquiring pronunciation accuracy and efficiency in the English language by ESL and EFL learners are essential. Yet, this is a challenge affecting Arab Yemeni learners as studies have shown that Arab Yemeni learners face difficulties in pronouncing English initial and final consonant clusters. This study investigates the pronunciation of English consonant clusters by young Yemeni EFL learners and the difficulties faced in pronouncing English consonant clusters. This case study employed an intervention for a total of four weeks with 8 young Yemeni participants. The respondents were introduced to basic phonology system and taught to recognise the differences between English and the Yemeni sound systems, participated in listening sessions to a native speaker for using English consonant clusters segments and practised choral repetition and self-correction using audio recordings. The American accent is targeted in this study as it is easier to be acquired by the English Yemeni learners. The respondents’ pronunciation was transcribed with the PRATT software to show the degree of differences between the pre- and post-study results after conducting the phonology course intervention. The study shows many developmental differences in pronouncing English consonant clusters after conducting four phonological training techniques which the Yemeni learners went through. This study would assist and provide a guide to Yemeni EFL learners and educators to address the difficulties of pronouncing English consonant clusters.